Answer:
[tex]y=\displaystyle-\frac{1}{2}x-\displaystyle\frac{1}{2}[/tex]
Step-by-step explanation:
Hi there!
Slope-intercept form: [tex]y=mx+b[/tex] where m is the slope and b is the y-intercept (the value of y when x is 0)
1) Plug in the slope (m)
We're given that the slope is [tex]\displaystyle-\frac{1}{2}[/tex]. In [tex]y=mx+b[/tex], replace m with [tex]\displaystyle-\frac{1}{2}[/tex]:
[tex]y=\displaystyle-\frac{1}{2}x+b[/tex]
2) Determine the y-intercept (b)
[tex]y=\displaystyle-\frac{1}{2}x+b[/tex]
We're given the point (-9,4). Plug this point into the equation as [tex](x,y)[/tex] and solve for b:
[tex]4=\displaystyle-\frac{1}{2}(-9)+b\\\\4=\displaystyle\frac{9}{2}+b[/tex]
Subtract [tex]\displaystyle\frac{9}{2}[/tex] from both sides to isolate b:
[tex]4-\displaystyle\frac{9}{2}=\displaystyle\frac{9}{2}+b- \displaystyle\frac{9}{2}\\\\\displaystyle-\frac{1}{2} = b[/tex]
Therefore, the y-intercept is [tex]\displaystyle-\frac{1}{2}[/tex]. Plug this back into [tex]y=\displaystyle-\frac{1}{2}x+b[/tex] as b:
[tex]y=\displaystyle-\frac{1}{2}x+(\displaystyle-\frac{1}{2})\\\\y=\displaystyle-\frac{1}{2}x-\displaystyle\frac{1}{2}[/tex]
I hope this helps!